THE EFFECTS OF INTELLECTUAL CAPITAL ON ORGANISATIONAL AGILITY: THE ROLE OF KNOWLEDGE SHARING AS MEDIATION - Wahyudi Wahyudi; Pemilia Sulistyowati; Setia Iriyanto; Heri Poerbantor; Sukamto Sukamto (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to determine and to evaluate the moderating effects of the relationship between Intellectual Capital, Knowledge Sharing, and Organizational Agility. This study surveyed 146 consumers in the city of Semarang, Central Java, who met specific requirements, including being female and at least 17 years old. By visiting women's forums and groups and completing online (Google form) and offline (print out sheets) questionnaires, primary data was collected directly from the source. This study used Partial Least Square (PLS) 3.0 as its data analysis approach. Intellectual Capital has a significant, positive, and powerful effect on Knowledge Sharing. This implies that if Intellectual Capital increases, so does Knowledge Sharing. It is acknowledged that Intellectual Capital has a strong, positive, and significant effect on Knowledge Sharing. This implies that as Intellectual Capital increases, so will Knowledge Sharing. Organizational Agility has a strong, positive, and significant relationship with Knowledge Sharing. This implies that if Intellectual Capital increases, so does Knowledge Sharing. Knowledge Sharing mediates the relationship between Intellectual Capital and Organizational Agility to a moderate degree.